A review of novel methods for Diuron removal from aqueous environments - Ghorban Asgari; Hossein Abdipour; Amir Mohammad Shadjou (Heliyon, 2023)
Runoff from intensive agriculture, which contains many sources of pollutants, including herbicides, for instance, Diuron, has threatened the environment and human health. The intrusion of these toxins into water sources poses a serious challenge to human society, and the rising release of these toxins has always been of concern to water researchers. The consequences of the release of these toxins into water sources are destructive and debilitating to human life. Today, the contamination of surface water and wastewater by pesticide residues, especially from agricultural activities and pesticide factories, has grown significantly. One of the pesticides commonly applied around the world is Diuron. There are various techniques for removing Diuron, the most important of which are adsorption and advanced oxidation. This review presents the characteristics, mechanisms, and emerging methods of removing Diuron. The use of absorbents, such as sludge-derived modified biochar (SDMBC600) and bottom ash waste (BAW-200), is discussed in detail. Additionally, the main features, benefits, and limitations of new technologies like hydrodynamic cavitation are enumerated. The effectiveness of novel adsorbents in Diuron removal is also discussed.